Studi tentang Kemampuan Teknik Dasar Sepak Bola - Muhammad Suhdy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the mastery of the techniques of passing, control, dribbling and shooting students of SMP Negeri 2 Lubuklinggau. This type of research is descriptive qualitative. The population in this study were all students who took part in soccer extracurricular activities totaling 20 people. The sampling technique uses total sampling technique. Data were collected using measurements of all three variables, tests conducted were tests of passing, control and dribbling. Data were analyzed with descriptive statistics namely frequency tabulation. The results of the study, based on the analysis of passing and controlling test data, found that out of 20 students, none had passing and control in either category, and 8 students (40%) had abilities in the Medium category and 12 students (60%) has the ability to pass and control in the category of Less. While the dribbling ability of 20 students, obtained 4 students (20%) have dribbling ability in the Good category, and 9 students (45%) have dribbling ability in the Medium category and 7 students (35%) are included in the Poor category. For kicks (shooting) students who have the Very Good category are as many as 2 people (10%) and the Good category are as many as 3 people (15%) and those who have a Fair category are as many as 8 people (40%) and 5 people (25 %) has Very Less Shooting ability. Conclusion, it still needs to be improved in basic soccer technical training. Keywords: Ability, Basic Football Techniques